Mycobacterium tuberculosis infection may increase the degrees of malignancy in lung adenocarcinoma - Li, Shanshan; Feng, Mengru; Wang, Fenghua; Liu, Dongxu; Li, Mingyan; Dai, Jinlong; Yang, Yan; Chai, Yinghui; Chen, Wen (Frontiers in Immunology, 2025)
BackgroundThe early diagnosis and management of lung adenocarcinoma co-existing with tuberculosis (LAC-TB) presents significant challenges in clinical settings. This is compounded by a paucity of robust clinical evidence elucidating the interactions between these two conditions.MethodsThis study included 14 patients diagnosed with LAC-TB, with an equal distribution among those with pulmonary tuberculosis (TB) and those with peripheral lymph node TB. Controls included patients with simple TB and those with lung adenocarcinoma (LAC). Histopathologic examinations confirmed typical changes in each group. Immunohistochemistry analyzed immune markers, focusing on PD-L1, while genomic analysis identified differential mutant genes.ResultsPathological evaluations showed that LAC-TB and LAC groups expressed TTF-1 and Napsin A in their adenocarcinoma specimens. Notably, a higher proportion of patients in the LAC-TB group had a Ki-67 proliferation index of ≥10%. Subsequent Molecular analyses revealed significant differences in RALGAPA1 gene expression, with the LAC-TB group also exhibiting a greater median count of missense mutations, single nucleotide polymorphisms, and overall mutations, suggesting a higher malignancy level than the LAC group. Additionally, the LAC-TB group showed an increased tumor mutational burden, indicating a potentially better response to immunotherapy. Immunohistochemical assessments indicated that Mycobacterium tuberculosis (MTB) infection correlated with reduced infiltration of T cells and CD4+ T cells, alongside an upregulation of PD-L1 expression in LAC. Notably, PD-L1 was strongly expressed in the TB granuloma and surrounding areas.ConclusionOur findings suggest that MTB infection may increase the malignancy of LAC, with the pronounced expression of PD-L1 in granuloma regions constituting a pivotal mechanism underlying this relationship.